2014
DOI: 10.1017/s0033291713003140
|View full text |Cite
|
Sign up to set email alerts
|

The contribution of familial internalizing and externalizing liability factors to borderline personality disorder

Abstract: Background Individuals with borderline personality disorder frequently display comorbid mental disorders. These disorders include “internalizing” disorders (such as major depressive disorder and anxiety disorders) and “externalizing” disorders (such as substance use disorders and antisocial personality disorder). It is hypothesized that these disorders may arise from latent “internalizing” and “externalizing” liability factors. Factor analytic studies suggest that internalizing and externalizing factors both c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
9
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 63 publications
3
9
1
Order By: Relevance
“…Despite their strong association with distress‐mediated disorders, particularly depression, it is important to note that rates of externalizing (e.g., substance use) and fear (e.g., phobias) disorders have been shown to be elevated among individuals with EDs as well. BN has been associated with high rates of substance use disorders as well as borderline personality disorder, which is considered to encompass both internalizing and externalizing facets of psychopathology . Nonetheless, our results and those of previous studies suggest that EDs may be most strongly associated with disorders characterized primarily by negative affect, worry, and rumination.…”
Section: Discussioncontrasting
confidence: 58%
See 1 more Smart Citation
“…Despite their strong association with distress‐mediated disorders, particularly depression, it is important to note that rates of externalizing (e.g., substance use) and fear (e.g., phobias) disorders have been shown to be elevated among individuals with EDs as well. BN has been associated with high rates of substance use disorders as well as borderline personality disorder, which is considered to encompass both internalizing and externalizing facets of psychopathology . Nonetheless, our results and those of previous studies suggest that EDs may be most strongly associated with disorders characterized primarily by negative affect, worry, and rumination.…”
Section: Discussioncontrasting
confidence: 58%
“…BN has been associated with high rates of substance use disorders 2 as well as borderline personality disorder, 25 which is considered to encompass both internalizing and externalizing facets of psychopathology. 26 Nonetheless, our results and those of previous studies 5,6 suggest that EDs may be most strongly associated with disorders characterized primarily by negative affect, worry, and rumination. Taken together, extant results underscore the importance of the role that depressive symptomatology, and affect regulation more generally, 27,28 may play in the development and maintenance of disordered eating.…”
Section: Discussionsupporting
confidence: 47%
“…However, these family study findings could not in themselves differentiate the proportion of etiological variance contributed by genetic and focus.psychiatryonline.org FOCUS Spring 2013, Vol. They found a range of heritability from 44%-60%, with the remaining variance contributed by individual specific environmental factors (18,60,92). 2 environmental factors (already outlined above).…”
Section: Early Developmentmentioning
confidence: 87%
“…Moreover, within the nosological superstructure of internalizing versus externalizing dimensions it appears to occupy some space of its own, whereby it combines characteristics of both (16)(17)(18). Where it belongs in the classification system is one such issue.…”
Section: Controversiesmentioning
confidence: 99%
“…The internalizing/externalizing model has proven to be useful for characterizing Axis I disorders in DSM-IV classification and could be linked to and translated to personality structure (James & Taylor 2008, Krueger et al 2001. Moreover, studies have reported that the covariation between internalizing and externalizing dimensions may be clearer after examining the connection between personality and these features and that internalizing and externalizing factors both contribute to BPD (Hudson et al 2014). Additional findings showed that neuroticism as a personality trait is an inherited marker of both internalizing and externalizing pathologies (Hink et al 2013).…”
Section: Discussionmentioning
confidence: 99%